∴an+2-an+1=2(an+1-an),
∵a1=1,a2=3,
∴
an+2-an+1 |
an+1-an |
∴{an+1-an}是以a2-a1=2為首項(xiàng),2為公比的等比數(shù)列.
(Ⅱ) 由(Ⅰ){an+1-an}是以a2-a1=2為首項(xiàng),2為公比的等比數(shù)列
得an+1-an=2n(n∈N*),
∴an=(an-an-1)+(an-1-an-2)++(a2-a1)+a1
=2n-1+2n-2++2+1
=2n-1(n∈N*).
(Ⅲ)證明:∵4b1-14b2-14bn-1=(an+1)bn,
∴4b1+b2+…+bn-n=2nbn
∴2[(b1+b2+…+bn)-n]=nbn,①
2[(b1+b2+…+bn+bn+1)-(n+1)]=(n+1)bn+1.②
②-①,得2(bn+1-1)=(n+1)bn+1-nbn,
即(n-1)bn+1-nbn+2=0.③
nbn+2-(n+1)bn+1+2=0.④
④-③,得nbn+2-2nbn+1+nbn=0,
即bn+2-2bn+1+bn=0,∴bn+2-bn+1=bn+1-bn(n∈N*),
∴{bn}是等差數(shù)列.